Estimation of Stock Status Using CMSY Method for the Sword Prawn (Mierspenaeopsis hardwickii) in Samboja Waters, East Kalimantan - Nadya Damayanthi Safitri; Ali Mashar; Rahmat Kurnia (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2026)
In this study, as a data-poor fish stock assessment method CMSY was used to assess the current stock status of the Sword Prawn in Samboja Waters. A total of 13 years catch data (from 2012 to 2024) was used in the analysing process of study. Estimated CMSY model parameters with confidence intervals are as folloe: r=0.47 (0.29-0.7) year-1, k=14.9 (10.1-22) ton, MSY=1.75 (1.23-2.36) ton, B2024=4.2 (0.43-5.89) ton, BMSY=7.45 (5.05-11) ton, F2024=0.28 (0.2-2.71) year-1, FMSY=0.23 (0.14-0.38) year-1, B2024/BMSY=0.56 (0.05-0.79) and F2024/FMSY=1.18 (0.84-11.4). Our study has found that sword prawn population in Samboja waters has been decline due to overfishing since 2017. Until now, regulations regarding catch quotas have not been established or implemented. Therefore, it is recommended to create regulations related to catch quotas based on research findings and reduce fishing mortality to maintain populations and prevent further biomass decline.